Vida útil de caju tratado na pré-colheita com giberelina e, na pós-colheita, com luz pulsada - Oliveira, Izabella Maria Costa (2024)
The cashew tree plays a significant role in the regional economy of the Northeast, providing employment and income opportunities in areas where it is cultivated. As it is a non-climacteric fruit, it must be harvested when it has reached full maturity. However, the high perishability of cashews has an impact on both the marketing of the product and its consumption as a fresh foodstuff. It is therefore necessary to employ pre- and post-harvest technologies in order to extend the shelf life and maintain the quality of cashews. The objective of this study was to extend the shelf life of CCP 76 cashews through the ombined application of gibberellic acid (GA3), pulsed light (PL), and film coating in storage at 3 ± 1 °C. In the field, the stalks were marked and sprayed at the onset of ripening (stage 1, green nut and stalk) and harvested at the full ripening stage (stage 7, when the stalk and nut were fully ripe). Subsequently, the cashews that received the pulsed light treatment were irradiated with flashes of broad spectrum light (200 to 1100 nm) lasting 0.3 ms and two pulses with a dose of 0.6 J/cm². The cashews from the control treatment were placed in trays and wrapped in ordinary PVC film, while those from the GA3 and GA3 + LP treatments were wrapped in PVC film with nano-silver. Subsequently, all the cashews were transferred to a cold room where they were stored at a temperature of 3 ± 1 °C and evaluated over the course of a month. The fruits treated with GA3 and GA3 + LP exhibited reduced mass loss, lower SS content, and enhanced firmness, indicating improved conditions for consumption and marketing for up to 15 days. LP exerted a pronounced influence on the enzymes evaluated and on the appearance of the cashews. The GA3 treatment appeared to modulate the activity of the enzymes IVA and IVN, as evidenced by the consistently lower activity of these enzymes throughout the experiment.